Advances in 1, 2, 4-triazepines chemistry. Issue 129 (16th December 2015) - Elattar, Khaled M.; Abozeid, Mohamed A.; Mousa, Ibrahim A.; El-Mekabaty, Ahmed
Abstract : This review reports the chemistry of 1, 2, 4-triazepines. Heterocyclic 1, 2, 4-triazepines are mono and fused cycles. Abstract : This review reports the literature survey of 1, 2, 4-triazepines. The investigated heterocycles are monocyclic and fused 1, 2, 4-triazepines. The different sections cover theoretical calculations of conformations and tautomerism, and synthesis and reactions of monocyclic and fused heterocycles incorporating 1, 2, 4-triazepines. The biological evaluation of the target compounds and related compounds is described, as well as the synthetic applications. The reaction mechanisms are discussed. The bibliography includes 152 references.